FROM KESSEL TO BUÑUEL AND OLIVEIRA: WHEN FILM RESPONDS TO LITERATURE - Bello, Maria do Rosário Lupi (Laboratório Editorial FCL-UNESP, 2012)
This paper compares and analyzes three different works which interact with each other: the novel Belle de Jour (1928) by Joseph Kessel and two films related to it, Belle de Jour, by Luis Buñuel (1967) and Belle Toujours by Manoel de Oliveira (2006). The aim is to understand the several dimensions implied in the process of semiotic transcodification operated by both filmmakers. A slippage of meaning, along with the formal changes that take place in the transfer of the written work to Buñuel’s film, is intensified in the film by Oliveira, who, although explicitly wishing to establish a dialogue with Buñuel’s film, finally reveals a continuity going back to the literary origin of the whole process. Thus, Oliveira’s final work testifies the intertextuality already present in the preceding film by rendering a more complex dialogue through the response given both to the suggestions embodied in the film and to the hidden meanings it carries. In this way, a new dynamics of exchange is established among the three works which facilitates  a permanent re-reading of each work, shedding simultaneously new light on the phenomenon of film adaptation and interarts relationship, namely between literature and film.